2010
DOI: 10.1007/s00167-010-1335-6
|View full text |Cite
|
Sign up to set email alerts
|

May smokers and overweight patients be treated with a medial open-wedge HTO? Risk factors for non-union

Abstract: Within this study, it could be demonstrated that the rate of non-union in medial open-wedge HTO is not higher than in the lateral closed-wedge technique. Concerning the detected risk factors, the importance of the preservation of the lateral cortex is emphasised. In addition, it is necessary to discuss the risk of non-union with smokers and overweight patients when planning the therapy. Finally, it should be considered to perform iliac crest bone grafting in these high-risk patients a priori.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
142
5
13

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 160 publications
(168 citation statements)
references
References 36 publications
8
142
5
13
Order By: Relevance
“…Surprisingly, the combination of a BMI [ 30 kg/m 2 and disruption of the lateral cortical hinge [ 2 mm was not a risk factor for delayed or nonunion. Previously, others have suggested using additional iliac crest bone grafting in these patients, whom they considered high risk [10]. Based on our results, we do not believe this is necessary.…”
Section: Discussionsupporting
confidence: 46%
See 4 more Smart Citations
“…Surprisingly, the combination of a BMI [ 30 kg/m 2 and disruption of the lateral cortical hinge [ 2 mm was not a risk factor for delayed or nonunion. Previously, others have suggested using additional iliac crest bone grafting in these patients, whom they considered high risk [10]. Based on our results, we do not believe this is necessary.…”
Section: Discussionsupporting
confidence: 46%
“…In terms of clinical risk factors for nonunion, we found that smoking tobacco was the only significant predictor, a finding that others also have identified [10,12]. Some authors therefore do not advocate this surgical procedure in patients who use tobacco [8,17].…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations